Testing the Autxhentication Platform System Using the Mccall Model - Tito Ramadhan, Muhammad; Gunawan, Yanyan; Manaf, Khaerul; Purwanto, Heri; Perdana, Rangga Satria; Subaeki, Beki (CV. Generasi Intelektual Digital, 2024)
Information technology plays a crucial role in enhancing business efficiency and effectiveness through the implementation of systems and software. Software facilitates the rapid and accurate management and pro-cessing of data, supporting business processes and increasing competitiveness. Software testing, conducted by a Quality Assurance professional, is a critical phase to ensure compliance with specifications and user requirements, as well as to mitigate the risk of technical or functional issues.This research was conducted at PT. Walden Global Service (WGS), an IT/Software House consultancy. The focus of the study was on the application of blackbox/greybox methods and the McCall model in software testing, specifically for an authentication platform developed for PT Fazpass Integrasi Indonesia.The results of the testing involved quality factors such as Correctness, Reliability, Integrity, and Efficiency. Performance testing using GTMe-trix and JMeter provided significant success percentages. Additionally, Usability testing showed the com-pleteness of documentation that facilitates the handover process between WGS and the client.The imple-mentation of the McCall model assisted Quality Assurance in categorizing criteria and Test Case catego-ries, with the output being a presentation of success and failure. This helps minimize technical or function-al issues and provides specific recommendations to users or clients regarding the feasibility and need for further development based on the testing results of factors in the Product Operation aspect of the McCall model.